AIR POLLUTION LEVELS DETERMINATION USING METHODS OF LICHENINDICATION IN TOWN PĻAVIŅAS - Znotiņa, Olita; Trejakova, Rasma (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
An assessment of air quality in the town Pļaviņas area was made using the index of atmospheric purity (IAP). The survey area was divided into 39 units (0.5×0.5 km), in which 22 average lichen relives were analyzed according to LeBlanc and De Sloover method. Calculations show that the most polluted air is near the road to heavy traffic. After the index of atmospheric purity (IAP) study concluded that Plavinas dominated by medium and small air pollution zones.